2008
DOI: 10.1002/ijc.24042
|View full text |Cite
|
Sign up to set email alerts
|

Tuberculosis and subsequent risk of lung cancer in Xuanwei, China

Abstract: Tobacco and indoor air pollution from smoky coal are major causes of lung cancer in rural Xuanwei County, China. Tuberculosis has been suggested to increase lung cancer risk, but data from prior studies are limited. We conducted an analysis of data from a retrospective cohort study of 42,422 farmers in Xuanwei. In 1992, interviewers administered a standardized questionnaire that included lifetime medical history, including tuberculosis. Subjects were followed from 1976, with deaths from lung cancer ascertained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
90
2

Year Published

2009
2009
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 105 publications
(99 citation statements)
references
References 22 publications
3
90
2
Order By: Relevance
“…Adjustment for demographic characteristics, lung disease and tobacco use did not affect results. Interestingly, the association was especially pronounced in the first 5 years after TB diagnosis but remained strong 5–9.9 years and 10+ years after TB [77]. This was validated by the second study, recruiting in total 5,657 TB patients and 23,984 controls matched for age and sex between 1997 and 2008 [78].…”
Section: The Role Of Inflammationmentioning
confidence: 83%
“…Adjustment for demographic characteristics, lung disease and tobacco use did not affect results. Interestingly, the association was especially pronounced in the first 5 years after TB diagnosis but remained strong 5–9.9 years and 10+ years after TB [77]. This was validated by the second study, recruiting in total 5,657 TB patients and 23,984 controls matched for age and sex between 1997 and 2008 [78].…”
Section: The Role Of Inflammationmentioning
confidence: 83%
“…Further support for this idea is the fact that some other pathogens that used to cause severe acute human diseases but now, due to medical advances, cause relatively benign chronic infections are associated with cancers originating from the infected tissues. Examples of this include the association of lung cancer with Mycobacterium tuberculosis and Chlamydophila pneumoniae infection, [10][11][12] colorectal cancer with Streptococcus bovis and Staphylococcus infection, 13,14 and gallbladder cancer with chronic Salmonella typhimurium infection. 13 Another group of facts pointing to inflammation as a cancer predisposing factor are examples of cancer outgrowth from pathologies that involve noninfectious inflammatory conditions such as Barrett's esophagitis, chronic pancreatitis, inflammatory bowel diseases (ulcerative colitis and Crohn's disease), age-related inflammation of prostate tissue, and so on.…”
Section: Inflammation and Cancer Developmentmentioning
confidence: 99%
“…However, the evidence is inconsistent, with some reporting a positive association, whereas others have reported an insignificant association. [5][6][7][8][9][10][11] The temporal relationship between TB and lung cancer is also not clear. TB and lung cancer have a large public health impact, and therefore the association between these 2 diseases deserves detailed investigation.…”
mentioning
confidence: 99%
“…Some cohort studies have reported a positive association between TB and lung cancer. 10,11 However, these studies might not be able to yield generalizable results, because they were usually conducted in high-risk populations, such as heavy smokers, asbestos-exposed workers, or populations with a high indoor exposure to coal smoke.…”
mentioning
confidence: 99%